PRE-SERVICE TEACHERS’ PERCEPTIONS OF GENERATIVE AI USE IN ACADEMIC WRITING: A CASE STUDY - Mezza Deswatik; Putu Dian Danayanti Degeng (AKSELERASI: Jurnal Ilmiah Nasional, 2026)
This study investigates pre-service teachers’ perceptions of generative artificial intelligence (GenAI) in academic writing within the English Language Education program at University of Brawijaya. Key challenges in academic writing for pre-service teachers include grammatical accuracy, vocabulary development, and argumentation. GenAI tools have been proposed as potential solutions to these challenges, but their adoption raises concerns about effectiveness, ethical considerations, and the risk of over-reliance. Employing a qualitative case study design, data were collected through a structured questionnaire comprising Likert-scale ratings and open-ended written explanations from pre-service teachers who had completed teaching internships. The results indicate that all participants regarded GenAI as a beneficial supporting tool capable of enhancing grammatical precision, broadening academic vocabulary, structuring arguments, facilitating idea development, and providing constructive feedback during the revision process. Nevertheless, several challenges were also reported, such as the difficulty of assessing the reliability of AI-generated output, the struggle to preserve originality given the presence of AI detection tools, and the potential for excessive dependence on AI to weaken autonomous writing abilities. All participants further expressed shared concern that the lack of well-defined institutional policies contributes to ambiguity surrounding the ethical use of GenAI in academic settings. In light of these findings, it is recommended that higher education institutions establish clear regulations governing the appropriate use of GenAI in academic writing and incorporate digital literacy programs that enable pre-service teachers to engage with AI tools responsibly, ensuring that such tools serve as supportive aids rather than substitutes for independent critical thinking and writing competence.​​​​​​​​​​​​​​​​